Memórias e identidades de um terreiro de Candomblé: Ilé Ògún Anaeji Ìgbele Ni Oman - Àse Pantanal: a Nação Efon em Duque de Caxias RJ - Lima, Alexandre Mantovani de (2015)
The coming of african peoples to Brazil next to the indigenous and european traditions enabled the setting of culture and afro-brazilian religion. The memory preserved and represented through their myths, rituals, dances, songs, rhythms and language were resignified through ancestors worship, Inquices, Vodun and Òrìsàs configured as candomblé religion of nations Angola, Jeje, Ketu, Ijesa and Efon. Each of them brings similar traits, but also its specificities. The nation of candomble in Bahia Efon emerges through a small group of people who came from the town of Ekiti-Efon in Nigeria and expands to the southeast. The afro - brazilian yard, Ilé Ògún Anaeji Ìgbele Ni Oman - Àse Pantanal alongside other candomblé nations was significant in the history of holy people and continues to bring meaning in life of its adherents. It includes the group of terraces that are recognized belonging to the afro-brazilian candomblé. This nation lives on through the religious practices of its adherents preserving their identity and internalizing identity papers that secure ways of thinking and experiencing their religiosity. In contact with their ancestors and orisas, they determine stays and establish changes by choosing your Bàbálórìsàs and Ìyálórìsàs who run the yard keeping fixed the link between the two worlds: the material world and the spiritual world